2022
DOI: 10.21203/rs.3.rs-1520926/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of coexistence of stunting, wasting, and underweight among children under five years in the Gambia; evidence from 2019/20 Gambian demographic health survey: Application of multivariate binary logistic regression model

Abstract: Background Malnutrition is a scarcity or inappropriate consumption of energy and nutrients. It comprises both undernutrition and overnutrition. The present study is aimed to evaluate the relationship between undernutrition indicators of stunting, underweight, and wasting among those under five years given other predictors. Method The data was obtained from the measure of DHS program. A total of 2,399 in 2019/20 under-five children were involved in this study. A multivariate binary logistic regression model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The bivariate analysis revealed that there was no significant relationship between birth spacing and underweight. Despite using the same birth spacing cut-off (3 years) as this study, research in Ethiopian children (Asmare & Agmas, 2022;Hintsa & Gereziher, 2019) revealed differences, the study found an assocation between birth spacing and underweight. The research conducted in Ethiopia (Fenta et al, 2020) also did not find a significant relationship between birth spacing and underweight.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The bivariate analysis revealed that there was no significant relationship between birth spacing and underweight. Despite using the same birth spacing cut-off (3 years) as this study, research in Ethiopian children (Asmare & Agmas, 2022;Hintsa & Gereziher, 2019) revealed differences, the study found an assocation between birth spacing and underweight. The research conducted in Ethiopia (Fenta et al, 2020) also did not find a significant relationship between birth spacing and underweight.…”
Section: Resultsmentioning
confidence: 73%
“…In this study, stunting was experienced by 71.4% of underweight children, while thin/wasting was indicated by only 9% of underweight children (p<0.005). A significant relationship between underweight and stunting was also discovered in a study of 2399 children in Gambia (Asmare & Agmas, 2022). The majority of children who are underweight are suffering from stunting, which has long-term health consequences.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation